Homelessness, nature, and health: toward a feminist political ecology of masculinities. Issue 7 (3rd July 2017) - Rose, Jeff; Johnson, Corey
Abstract: Engaging with feminist political ecology and leveraging experiences from a 16-month critical ethnography, this research explores ways in which masculinities served as both a rationale and an outcome of men facing homelessness living in the margins of an urban municipal public park – a space known as 'the Hillside.' Ethnographic narratives point to Hillside residents making their home in nature, connecting experiences in nature with various masculinities, and the gendered eschewing of social services. These portrayals further highlight the perceived feminization of social services within a context of rapidly neoliberalizing urban environments, and illustrate the ways participants positioned and engaged with social services. Entanglements of health and nonhuman nature prompt a feminist political ecological engagement with masculinity. Experiences from the Hillside add textured richness to discourses concerning the ways in which contemporary landscapes are constructed, perceived, experienced, and co-constituted through and with gender.